Boganmeldelser - Anttila, Inkeri; Kristmundsson, Omar H.; Zila, Josef; Flyghed, Janne; Pedersen, Jørge Dige; Brøndsted, Henning; Kyvsgaard, Britta; Baldursson, Erlendur S.; Pedersen, Jan; Storgaard, Anette; Greve, Vagn; Rekke, Nils (Nordisk Tidsskrift for Kriminalvidenskab, 1992)
Book reviews